2018
DOI: 10.1111/fme.12318
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of global climate change on fisheries in the Trasimeno Lake (Italy), with special reference to the goldfish Carassius auratus invasion and the endemic southern pike Esox cisalpinus decline

Abstract: Global climate changes have led to a gradual warming of the planet, resulting in decreased precipitation and rising temperatures in Mediterranean inland waters. In Trasimeno Lake, the largest shallow lake in Italy, some non‐native fish species have probably benefited from these changes as they are thermophilic and characterised by wider habitat preferences. Fish data collected by gillnets and fyke nets between 1956 and 2016, and by electrofishing in 1993 and 2014, were used to analyse changes over time in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As reported for other watersheds in the Mediterranean area [70], also in the Tiber River basin the longitudinal gradient was associated with a progressive decline in water quality, proceeding from upstream to downstream, demonstrated by the decrease of EBI and increased conductivity and concentration of dissolved salts. Beside this, recent studies carried out in the Tiber river basin [28,71] showed the presence of many invasive species, mainly located in lowland stream reaches and lakes [72,73]; these species are often limnophilous and can be favored by climate changes due to their wider ecological tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…As reported for other watersheds in the Mediterranean area [70], also in the Tiber River basin the longitudinal gradient was associated with a progressive decline in water quality, proceeding from upstream to downstream, demonstrated by the decrease of EBI and increased conductivity and concentration of dissolved salts. Beside this, recent studies carried out in the Tiber river basin [28,71] showed the presence of many invasive species, mainly located in lowland stream reaches and lakes [72,73]; these species are often limnophilous and can be favored by climate changes due to their wider ecological tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of MPs in GITs is directly dependent not only on their ingestion but also on the retention time of particles in digestive systems (Bour et al, 2020), which is relatively short and influenced by the physical characteristics of MPs, such as size and shape, the presence of food, the gut length, and digestion period (Jabeen et al, 2018;Rochman et al, 2019). Experimental and field studies demonstrated that fibershaped microplastics, ingested by amphipods, require longer clearance times than spheres (Ma et al, 2020), and MPs fibers ingested by crabs and lobster can result in the formation of fibrous aggregates within the gut and a reduction in egestion efficiency (Au et al, 2017;Carosi et al, 2019;Cau et al, 2019). Other biological factors, such as size of organisms, may affect the likelihood of microplastic ingestion: larger individuals consume more; in general, due to increased energy demands, therefore, the potential for ingestion of plastic particles may increase as well (Horton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Trasimeno Lake is the largest one in Central Italy (Umbria Region) with a surface of 126 km 2 and an average depth of 4.7 m. It is a closed laminar lake without natural tributaries, and its hydrological regime depends on local rainfall, typically maximum in autumn and minimum in summer (Tavoloni et al, 2021). In addition to these peculiar features, the Trasimeno Lake is exposed to a limited anthropogenic pressure (Carosi et al, 2019): settlements are not very high in terms of equivalent inhabitants, the civil discharges are subjected to an efficient purification, and most of them are collected outside the lake basin. Even the isolated uncollected drains are not relevant and, to a large extent, are self-purified from the drainage network before they reach the lake (PSR Umbria, 2013).…”
Section: Study Areasmentioning
confidence: 99%
See 2 more Smart Citations